(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1993)
A model, generalizing the rigid body problem is considered. An integrable case is isolated. The topology of the real level sets of the motion constants and all bifurcations of the Liouville tori and cylinders are described.